2011
DOI: 10.1002/jso.21943
|View full text |Cite
|
Sign up to set email alerts
|

The clinical use of indocyanine green as a near‐infrared fluorescent contrast agent for image‐guided oncologic surgery

Abstract: Optical imaging using near-infrared (NIR) fluorescence provides new prospects for general and oncologic surgery. ICG is currently utilised in NIR fluorescence cancer-related surgery for three indications: sentinel lymph node (SLN) mapping, intraoperative identification of solid tumours, and angiography during reconstructive surgery. Therefore, understanding its advantages and limitations is of significant importance. Although non-targeted and non-conjugatable, ICG appears to be laying the foundation for more w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
610
0
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 711 publications
(626 citation statements)
references
References 114 publications
1
610
0
15
Order By: Relevance
“…If radiolabeled with 99m Tc, the SLN at the time of surgery would not contain a detectable amount of radioactivity. The solution to these and other scenarios is to label tilmanocept with a fluorescent reporter and perform SLN mapping with a handheld optical imaging system (18). An additional setting compatible with an optical reporter is robot-assisted surgery (19), where near-infrared-capable imaging systems are integrated into the three-dimensional viewing console (20); mapping in this setting would follow single photon emission computed tomography (SPECT) S entinel lymph node (SLN) mapping (1) of breast cancer (2,3) and melanoma (4) is well validated (5-7) and has become standard procedure in the determination of whether these cancers have metastasized to regional lymph nodes.…”
Section: Synthesis and Characterization Of Optically Labeled Tilmanoceptmentioning
confidence: 99%
“…If radiolabeled with 99m Tc, the SLN at the time of surgery would not contain a detectable amount of radioactivity. The solution to these and other scenarios is to label tilmanocept with a fluorescent reporter and perform SLN mapping with a handheld optical imaging system (18). An additional setting compatible with an optical reporter is robot-assisted surgery (19), where near-infrared-capable imaging systems are integrated into the three-dimensional viewing console (20); mapping in this setting would follow single photon emission computed tomography (SPECT) S entinel lymph node (SLN) mapping (1) of breast cancer (2,3) and melanoma (4) is well validated (5-7) and has become standard procedure in the determination of whether these cancers have metastasized to regional lymph nodes.…”
Section: Synthesis and Characterization Of Optically Labeled Tilmanoceptmentioning
confidence: 99%
“…Recently, there has been considerable focus on the potential use of indocyanine green (ICG) in intraoperative real-time imaging [10][11][12][13][14][15][16]. However, the strong binding of plasma proteins with ICG and its subsequent rapid clearance by the liver results in binding of ICG to the tumor only for a short duration after administration; thus, the use of ICG for tumor imaging applications is limited [17].…”
Section: Introductionmentioning
confidence: 99%
“…8a. Recently, ICG fluorescence imaging has been attracting attention, and it is expected to be a novel tool to detect SNs [17,18]. Tajima et al [19,20] reported on intraoperative ICG fluorescence imaging using a charge-coupled device camera with a light-emitting diode (Hamamatsu Photonics, Hamamatsu, Japan).…”
Section: Resultsmentioning
confidence: 99%